2008
DOI: 10.1016/j.pec.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Physician–patient communication in single-bedded versus four-bedded hospital rooms

Abstract: The research findings indicate the relevance of taking account of the context in which physician-patient communication takes place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 16 publications
0
33
0
1
Order By: Relevance
“…The literature suggests that ill patients wanted nurses to be closer. 12,13,42 Some patients in our study reported a high level of connection with staff, with staff perceived to be giving them full attention, listening and interested in the patient as a person, while others felt a sense of disconnection. A study of cancer patients in Denmark 68 found that refuge from fellow patients was hard to achieve in multibedded rooms and the fact that personal conversations might be overheard by fellow patients caused important information to be withheld from health-care professionals.…”
Section: Design Implicationsmentioning
confidence: 79%
See 1 more Smart Citation
“…The literature suggests that ill patients wanted nurses to be closer. 12,13,42 Some patients in our study reported a high level of connection with staff, with staff perceived to be giving them full attention, listening and interested in the patient as a person, while others felt a sense of disconnection. A study of cancer patients in Denmark 68 found that refuge from fellow patients was hard to achieve in multibedded rooms and the fact that personal conversations might be overheard by fellow patients caused important information to be withheld from health-care professionals.…”
Section: Design Implicationsmentioning
confidence: 79%
“…29 In other studies, patients rated privacy and personal space as important but they also said that when ill they wanted nurses to be closer. 12,13,42 There is also evidence of more speech privacy and higher patient-reported satisfaction with doctor and nurse communication in single room patient accommodation. 11 A study of patient-physician communication in the Netherlands suggested that patients find it easier to raise questions with staff during ward rounds in single rooms than in multibedded rooms and feel that staff are more empathetic towards them.…”
Section: Box 1 Advantages and Disadvantages Of Single Rooms For Patiementioning
confidence: 99%
“…This change seems to have come about from the combination of three separate, but interrelated, interventions: firstly, moving from a very hierarchical structure -with physicians standing and patients lying downtowards a more equal perspective where both sit in a chair facing each other; secondly, using a special room allowing privacy during the round conversation; and thirdly, having the physicians meet the patient together with the nurse and the nurse assistant. Physician-patient communication in single-bedded versus four-bedded hospital rooms was studied by van de Glind and colleagues [13] . They concluded that single rooms seemed to contribute to physician-patient communication in a positive way since patients asked more questions and affective reactions from physicians were more frequent in single rooms.…”
Section: Discussionmentioning
confidence: 99%
“…Large variation between physicians time-motion patterns during walking rounds was also reported using real-time location systems [39] . Research showed that single-room rounding took longer time compared to rounding four-bedded rooms [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation